Inhaled particles VI : proceedings of an International Symposium and Workshop on Lung Dosimetry organised by the British Occupational Hygiene Society in co-operation with the Commission of the European Communities, Cambridge, 2-6 September 1985 - Dodgson, J. (Pergamon Press, 1988)
Inhaled Particles VI contains the proceedings of an international symposium and workshop on lung dosimetry, organized by the British Occupational Hygiene Society in cooperation with the Commission of the European Communities and held at Cambridge on September 2-6, 1985. The symposium presents results of research on the entry, destiny, and effects of respired particles, with emphasis on mechanisms and dose-response relationships. This book contains, in three separate parts, 84 papers from the symposium, 34 workshop papers, and 20 poster presentations. Parts 1 and 2 are further divided into sect.